PROFESSIONAL READINESS OF FUTURE SPECIAL EDUCATION TEACHERS FOR INCLUSIVE EDUCATION IN UKRAINE - Мartynchuk Olena; Skrypnyk, Tatiana; Maksymchuk, Mariia; Babych, Nataliia; Biriukova, Karina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article is devoted to the problem of compliance of special education teachers training in Ukraine with the implementation of inclusive education in accordance with international standards. It was found that despite many years of inclusive policy experience in Ukraine, inclusive practice is not implemented properly. The assumptions about gaps in the staffing of inclusive education are made. The level of professional readiness among future special education teachers for practice in inclusive educational environment is investigated and analyzed in the article. The comprehensive questionnaire developed by the authors was used as a diagnostic tool in current study. The questionnaire was designed in accordance with the content of such educational guidelines as the “Professional Development Tool for Improving the Quality of Work of Primary School Teachers” and the “Profile of Inclusive Teachers”. The main professional readiness criteria for practice in inclusive educational environment among future teachers are defined: Interactions; Family and Community; Inclusion, Diversity, and Values of Democracy; Assessment and Planning; Teaching Strategies; Learning Environment; Professional Development. The developed questionnaire is aimed to identify the level of development of different professional readiness components, such as: theoretical-cognitive and practical-active. The results showed low and medium levels of professional readiness for practice in inclusive educational environment among future special education teachers, that is insufficient to meet the social demand for training specialists to work in the new professional conditions of inclusive education.Correlation analysis revealed the leading role of the practical-active component in the system of professional training, which require increased attention to its practical component, based on both university practical training centers and pedagogical internship. The current study concludes on the necessity of transformation of professional training content for future special education teachers in accordance with international scientific achievements in the field of providing quality services to children with special educational needs.